Pengembangan Papan Konversi Satuan Menggunakan Metode Jamping Materi Satuan Berat Dan Satuan Panjang - Mahmudi, Moh Rosyid; Subhan, Muhammad; Auliana, Rini (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Education is something that every human being needs to gain experience, knowledge, and skills to develop potential within him, so as to boost one's life for the better. In this study uses the type of research and development Research and Development (R&D). This development model consists of five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The population and sample of this study were conducted in class III at SDN 104/II Sungai Pinang with a total of 24 students. The type of data used in research is qualitative and quantitative. This research was conducted on conversion board learning media for mathematics material units of weight and units of length in class III SD. data collection instruments using validation sheets, practicality instruments, and effectiveness instruments. Data collection techniques using observation, interviews, documentation, and learning performance tests. The data analysis technique used uses three data analysis techniques, namely validity analysis, practicality analysis, and effectiveness analysis. The results of the study obtained the validity of the unit conversion board learning media as assessed by the validator, totaling 3 people, indicating that the conversion board learning media obtained a proportion of 86% with a very valid category. Practicality was assessed from the point of view of the teacher's response to the unit conversion board learning media filled out by educators at SDN 104/II Sungai Pinang obtaining a proportion of 100%. Effectiveness comes from the results of the effectiveness sheet filled in by students on the unit conversion board learning media obtaining a proportion of 83.34% with the very effective category.